Medical Student Ultrasound-Guided Intravenous Catheter Education: A Randomized Controlled Trial of Overtraining in a Simulation-Based Mastery Learning Setting. Issue 1 (February 2022) - Kule, Amy; Richards, Rasheed A.; Vazquez, Helen M.; Adams, William H.; Reed, Trent
Abstract : Introduction: Simulation-based mastery learning (SBML) improves skill transfer to humans. However, limited data exist to support the practice of performing additional training attempts once mastery has been achieved. We explored whether implementing this concept in an SBML model improves skill transfer in ultrasound-guided peripheral intravenous (USGPIV) catheter placement from simulator to humans. Methods: Forty-eight first- and second-year medical students underwent SBML for USGPIV placement to mastery standards on a simulator once to achieve minimum passing standard based on a 19-item checklist. Next, they completed either 0, 4, or 8 additional mastery level simulated performances in nonconsecutive order before attempting USGPIV placement on a human. An unplanned post hoc retention phase occurred 6 months later where participants' USGPIV skills were reassessed on a second human volunteer using the same checklist. Results: In this sample, the success rate among the 3 training cohorts did not improve as the number of additional training sessions increased (exact P = 0.60) and were comparable among the 3 cohorts (exact P = 0.82). The overall checklist performance was also comparable among the 3 cohorts (exact P = 0.57). In an unplanned (small) sample of returning participants, the USGPIV retention rate exceeded 80% for those originally assigned to 4 or 8 sessions, whereas the retention rate fell less than 50% for those originally assigned to control. Among these returning participants, the overall success rate was 58% on the initial assessment and was 68% on retention. Conclusions: In this sample of novices, we were unable to show that up to 8 additional mastery level performances of USGPIV placement on a simulator following SBML training improve skill transfer for both USGPIV placement success and total checklist performance.